Deformed K− nuclei in the Skyrme–Hartree–Fock approach. (23rd December 2019) - Jin, Yun; Chen, Chao Feng; Zhou, Xian-Rong; Cheng, Yi-Yuan; Schulze, H-J
Abstract: The properties of kaonic nuclei are studied using a two-dimensional Skyrme–Hartree–Fock model with a KN Skyrme force. We focus in particular on the instability of the solutions for a too strong KN interaction, which determines a maximum value of the kaon binding in this approach. We then analyze the change of the deformation properties of several core-deformed nuclei caused by the added kaon, and find a shrinking of the core and in some cases a complete loss of deformation.